The Effects of Hydrogen on Microstructural Change and Surface Originated Flaking in Rolling Contact Fatigue - Hideyuki Uyama (Japanese Society of Tribologists, 2011)
The effects of hydrogen on microstructural change and surface originated flaking in rolling contact fatigue were investigated using JIS-SUJ2 bearing steel specimens charged with hydrogen. Under clean lubrication conditions, subsurface originated flaking occurred and the rolling contact fatigue life was reduced and the amounts of the microstructural change called white structure that formed in the specimens increased as the hydrogen content increased. The localized microstructural changes were found in the hydrogen-charged specimens by electron microscope observations. It is supposed that the localization of plasticity was enhanced by hydrogen during the process of rolling contact fatigue. Under contaminated lubrication conditions, which included debris in the lubricating oil, surface originated flaking occurred and the rolling contact fatigue life of the hydrogen-charged specimens became shorter than the uncharged specimens, although white structure was not observed around the flaking. Enhancement of fatigue crack formations due to hydrogen was observed in specimens with artificial dents. It is presumed that hydrogen facilitated the formation of fatigue cracks on the raceway surface.